DISTRIBUSI SPASIAL DAN TEMPORAL IKAN SIDAT (Anguilla sp.) YANG BERMIGRASI KEHULU DI SUNGAI TINOMBO KABUPATEN PARIGI MOUTONG - Syahril, Mohamad (JSTT, 2016)
Eels (genus of Anguilla) has long been the object of intensive research. The province of Central Sulawesi has an abundant source of eel seeds (glass eel phase) especially from the species of Anguilla marmorata. The highest abundance of eel seeds occurs during the period of dark moon along the estuaries flowing to the Tomini Bay. The objectives of the research were to study the species diversity of eels (Anguilla sp.), to study the species composition of the eels, and to study the size structures of the eels (Anguilla sp.) migrating upstream to the River Tonombo. Identification of the eel samples was conducted by using morphometric method that was the ratio between predorsallength (PD) and anadorsallength (PA), and total length (TL). During sampling periods there were three species of eels identified migrated upstream to River Tinombo, and they were Anguilla marmorata, A. selebecensis, and one unknown species labelled as Anguilla sp. The species of A. marmorata had the highest abundance (86%). It was followed by A. celebecensis (10%) and Anguilla sp. (4%). Results showed that spatially the eels found in River Tinombo decreased in number but increased in their weight. While temporally, their abundance were different each month. It seemed that eels migrated upstream in order to grow.